PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS SCAFFOLDING UNTUK MEMAHAMKAN KONSEP FUNGSI PADA MAHASISWA - Arif Hidayatul Khusna (Yayasan Pendidikan Intan Cendekia, 2018)
New students get misconceptions about the function concept so that LKM are needed as a learning medium in an attempt to understand the concept of a new function. This study aims to describe how the development of LKM based Scaffolding to understand the concept of function in the new students are valid and practical. The development model used is Borg Gall (1983). Development model consisting of 4 stages, that are information gathering, planning, product development, and product testing. The research instrument used is LKM validation sheet and student response sheet. The results show that the LKM that developed had valid category with a score of 3.7 and the practical category with a score of 3.7.